The information content of the Islamic interbank money market rate in Malaysia - Kassim, Salina H.; Abdul Manap, Turkhan Ali (Emerald Group Publishing, 2008)
The purpose of this paper is to analyze the information content of the Islamic interbank money market rate (IIMMR), with respect to several macroeconomic indicators such as output, inflation, exports, imports, bank loans and stock market index, and compare it against that of the conventional interbank money market rate using the Malaysian data.